Policy Credibility and Sovereign Credit : The Case of New EU Member States - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 2007)
References to policy credibility, particularly with regard to fiscal policy, are ubiquitous in both economic literature and financial markets, even though it is not directly observable. The case of the EU new member states (NMS)-emerging markets joining a supranational entity that is generally considered to have higher policy credibility-provides a unique experiment to assess the effects of credibility on sovereign credit. This paper examines the impact of EU accession on three key variables that can reflect in varying degrees policy credibility: sovereign ratings, foreign currency spreads, and local currency yields. The results suggest that the NMS appear to have enjoyed higher credibility compared to their peers.